2018
DOI: 10.1055/s-0037-1613687
|View full text |Cite
|
Sign up to set email alerts
|

P3 Cognitive Potential in Cochlear Implant Users

Abstract: Introduction  The P3 cognitive evoked potential is recorded when a subject correctly identifies, evaluates and processes two different auditory stimuli. Objective  to evaluate the latency and amplitude of the P3 evoked potential in 26 cochlear implant users with post-lingual deafness with good or poor speech recognition scores as compared with normal hearing subjects matched for age and educational level. Methods  In this prospective cohort study, auditory cortical responses were recorded from 26 post-lingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Consistent with previous studies (e.g., Kubo et al, 2001;Beynon et al, 2005;Obuchi et al, 2012;Soshi et al, 2014;Grasel et al, 2018;Han et al, 2020), P300 amplitudes were significantly larger and latencies were significantly shorter for the NH group than for the CI group. For the present bimodal CI listeners, mean P300 amplitude and/or latency values were comparable to those observed in previous studies with CI listeners (e.g., Iwaki et al, 2004;Sasaki et al, 2009;Grasel et al, 2018;Abrahamse et al, 2021;Calderaro et al, 2020;Van Yper et al, 2020). P300 responses were elicited in all CI participants, consistent with Obuchi et al (2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies (e.g., Kubo et al, 2001;Beynon et al, 2005;Obuchi et al, 2012;Soshi et al, 2014;Grasel et al, 2018;Han et al, 2020), P300 amplitudes were significantly larger and latencies were significantly shorter for the NH group than for the CI group. For the present bimodal CI listeners, mean P300 amplitude and/or latency values were comparable to those observed in previous studies with CI listeners (e.g., Iwaki et al, 2004;Sasaki et al, 2009;Grasel et al, 2018;Abrahamse et al, 2021;Calderaro et al, 2020;Van Yper et al, 2020). P300 responses were elicited in all CI participants, consistent with Obuchi et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…Also, previous studies have shown more robust P300 responses with bimodal than with CI-only listening (e.g., Iwaki et al, 2004;Sasaki et al, 2009). Consistent with previous studies (e.g., Beynon et al, 2005;Obuchi et al, 2012;Grasel et al, 2018), we expected greater P300 amplitudes and shorter P300 latencies in NH than in CI listeners. Given the great variability in speech performance among CI users (e.g., Stickney et al, 2004;Cullington and Zeng, 2008) and given that P300 is sensitive to auditory task difficulty (Parasuraman and Beatty, 1980;Polich, 1987;Causse et al, 2016), we expected that P300 responses would be related to masked speech recognition, especially for the more difficult segregation of competing speech by CI users.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well known that meningitis impacts the cochlea and the central nervous system despite complete electrode insertion. 38 , 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding Cochlear Implant (CI) users, P300 may be useful to assess cognitive aspects, 2 , 3 , 4 predict the success of the CI surgery, 5 and elucidate post-CI surgery changes in auditory perception. 6 …”
Section: Introductionmentioning
confidence: 99%